Load insensitive radio frequency power amplifiers - Gonçalves, Cristiano Ferreira (2022)
Solid state power amplifiers (SSPAs) evolved significantly over the last few decades, mainly, due to the use of new transistor technologies, such as gallium nitride (GaN) high-electron-mobility transistors (HEMTs), very advanced computer-aided design (CAD) software, and very effective digital pre-distortion (DPD) algorithms. This led to a considerable performance improvement, in terms of energy efficiency, output power, and linearity. To achieve this performance, power amplifier (PA) designers normally push the used transistors very close to their physical safe operating limits, and consider them to operate for a fixed output load. However, the designed PAs are used for many different industrial and/or telecommunication applications, and, in some cases, such as, for example, microwave cooking or massive multiple-input multiple-output (MIMO) fifth generation (5G) base stations (BSs), the output load of these amplifiers can change. Under this nonoptimal scenario, the used transistors will operate for non-nominal loads, and the PAs performance can be severely degraded. Moreover, in highly optimized designs, where the transistors are operated close to their safe limits, their reliability can be reduced or, in extreme cases, they can even be permanently damaged. Therefore, load insensitive PA architectures, and/or techniques that aim at reducing the load variation seen by the PA, are necessary to improve the performance under load varying scenarios. This thesis presents various strategies to improve load insensitiveness of PAs. The presented techniques are based on tunable matching networks (TMNs) and on the amplifiers’ drain supply voltage (VDS) variation. The developed TMNs successfully reduced the load variation seen by the PA, and its performance was greatly improved, for non-optimal loading, by also using the derived load dependent VDS variation. These different approaches were tested and validated on single-ended PAs and then, based on their advantages and disadvantages, the most promising technique – the supply voltage modulation – was selected for the design of a Doherty power amplifier (DPA), which is of paramount importance for telecommunication applications. Moreover, since in some applications the output load variation can be unpredictable, we also developed a complete quasi-load insensitive (QLI) PA system that includes an impedance tracking circuit and an automatic real-time compensation of the amplifier performance.